(untitled) (Research, Society and Development, 2025)
Objective: To analyze knowledge and perception about Human Papillomavirus (HPV) vaccination among health students. Methods: This was a cross-sectional, descriptive study conducted between May and October 2024 with health students from different academic semesters in the state of São Paulo, Brazil. Data were collected using an online structured questionnaire applied through Google Forms®. Students who agreed with the informed consent form and completed all questions were included. Descriptive statistics with absolute and relative frequencies were performed. The study was approved by a Research Ethics Committee (CAAE: 70419923.8.0000.5492). Results: A total of 104 students participated; 80.8% were between 19 and 29 years old and 93.3% were medical students. Most reported having attended lectures on HPV (57.7%), although fewer reported clinical contact with infected patients (38.5%). Complete vaccination coverage was reported by 61.5%, while 24% had not been vaccinated. All participants considered the vaccine safe, and 95.2% supported mandatory vaccination for adolescents. Gaps were identified in knowledge of viral subtypes and vaccines available in the Brazilian public health system. Conclusion: Health students demonstrated a positive perception and adequate general knowledge regarding HPV infection and vaccination. However, specific weaknesses indicate the need for continuous educational strategies during undergraduate training to improve vaccination adherence and health communication.